Il matrimonio "sine opere coniugali" tra diritto e teologia (XII-XIII secolo) - Marchetto, Giuliano (Quaderni di storia religiosa medievale, 2020)
A marriage sine opere coniugali was legitimized by canon lawyers and theologians, but it was generally believed that there was no marriage without consent to carnal intercourse. This belief called into question the perfection of Mary and Joseph’s union. Therefore, the canonist Gratian posited that marriage was begun with consent but ratified only by sexual intercourse. Hence, lawyers and theologians began to dispute the perfection of an unconsummated marriage and to discuss nuptial consent. In this discussion, the juridical concept of potestas corporis played a central role.